02 Debate: a majority of lupus patients (will) need a biologic!. (1st September 2020) - Isenberg, David
Abstract : The mortality figures for lupus have improved from 50% 4-year survival in the 1950s to approximately 85% 15-year survival now. This change has resulted from the judicious use of steroids, immunosuppressive drugs, concomitant therapies, dialysis and transplantation; however, there seems little prospect that these figures will improve further. A Canadian study showed that lupus patients are still, overall, three times more likely to die than the rest of the population 1, a figure which increases to twelve times in those aged under 40 years old. A UK study showed the premature mortality gap in lupus has not closed in a recent 16-year period. 2 In addition to mortality, morbidity linked to the disease, concomitant diseases and treatment side-effects remain a big problem. Steroids in particular are a major culprit. As an example, myocardial infarction, infection and some cancers remain increased in lupus patients. In this debate, I will try to persuade you, using both data and the works of Cornelis Escher and Kathe Strenitz, that to improve both the longevity and quality of life of lupus patients, we must embrace new treatment paradigms including biologics and small molecules and whatever comes next! Biologic drugs such as rituximab have shown great benefit in the treatment of lupus 3 and in reducing, even abolishing, the need for concomitant steroids. 4 Other drugs like belimumab have demonstrated utility for lupus patients with joint, skin and renal disease. It is likely that other biologics identified more recently, such as anifrolumab, will have a part to play for those lupus patients for whom standard drugs are insufficient. 5 These changes will not happen today, tomorrow or next year, but in the next decade I predict that the majority of lupus patients will be treated with biologic drugs and newer treatment modalities. Learning Objectives: Explain the need for new biologic treatments for patients with lupus, for whom standard drugs have failed Describe the importance of embracing new evidence-based treatments including small molecules and biologics, for the numerous disease manifestations that characterise lupus Discuss the role of biologic therapies in future treatment of patients with lupus References: Tselios K, Gladman DD, Sheane BJ, et al . All-cause, cause-specific and age-specific standardised mortality ratios of patients with systemic lupus erythematosus in Ontario, Canada over 43 years (1971–2013). Ann Rheum Dis 2019;78(6) :802–06. Jorge AM, Lu N, Zhang Y, et al . Unchanging premature mortality trends in systemic lupus erythematosus: a general population-based study (1999–2014). Rheumatology (Oxford) 2018;57(2) :337–44. McCarthy EM, Sutton E, Nesbit S, et al . Short-term efficacy and safety of rituximab therapy in refractory systemic lupus erythematosus: results from the British Isles Lupus Assessment Group Biologics Register. Rheumatology (Oxford) 2018;57(3) :470–79. Condon MB, Ashby D, Pepper RJ, et al . Prospective observational single-centre cohort study to evaluate the effectiveness of treating lupus nephritis with rituximab and mycophenolate mofetil but no oral steroids. Ann Rheum Dis 2013;72(8) :1280–6. Murphy G, Isenberg DA. New therapies for systemic lupus erythematosus — past imperfect, future tense. Nat Rev Rheumatol 2019;15(7) :403–12.